The impact of processing methods on the quality of Sudanese white cheese produced by small scale in New Halfa area - I.A.E. ELKHIDER; I.E.M. El ZUBEIR; A.A. BASHEIR (Acta Agriculturae Slovenica)
This study was carried out to compare the effects of production and processing methods of Sudanese white cheese produced in small production units on cheese quality. The study was based on surveying 10 small scale producers in New Halfa area (eastern Sudan) during the period of February to July, 2008. The production was carried out mainly by private sector (70%), while 30% were owned by governmental institutes. Milk used in the cheese making was fresh cow milk purchased from nomads (90%) compared to only 10% from dairy farms. Regarding the level of education, 60% of cheese producers finished secondary school and 40% were university graduates. The average age of cheese producers ranged between 35–50 years. The results showed no variation between cheese manufacturing methods in the majority of production units in New Halfa. The supervision by the health authority comprised about 80% of production units. Significant (P < 0.05) variation was found in fat and ash content and non significant differences were observed for total solids, protein content and the acidity of the Sudanese white cheese due to variation in education, training, ownership, health visits, heat treatment and marketing methods. Moreover, the producers owing the plant for cheese processing produced cheese with significantly (P < 0.05) high counts for total bacteria, yeast, mould and coliform. However training and the regular health visits were found to improve the hygienic quality. The study suggested that interventions and training of cheese producers would help to improve Sudanese white cheese quality in New Halfa area. In conclusion, traditional cheese methods need to be encouraged and improved to utilize the surplus milk in rural areas.